2023
DOI: 10.1186/s12916-023-02743-8
|View full text |Cite
|
Sign up to set email alerts
|

Maternal pre-pregnancy body mass index is associated with newborn offspring hypothalamic mean diffusivity: a prospective dual-cohort study

Abstract: Background An extensive body of animal literature supports the premise that maternal obesity during pregnancy can alter the development of the fetal hypothalamus (HTH, a critical regulator of energy balance) with implications for offspring obesity risk (i.e., long-term energy imbalance). Yet, the relationship in humans between maternal overweight/obesity during pregnancy and fetal hypothalamic development remains largely unknown. Here, using an international (Finland and California, USA) multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 52 publications
0
20
0
1
Order By: Relevance
“…32 A prospective human dual-cohort study observed an approximately linear association between maternal pre-pregnancy BMI and offspring hypothalamic microstructure on MRI images, further demonstrating the plasticity of prenatal hypothalamic development in the context of maternal overnutrition during pregnancy. 33 Interestingly, in the present study, the hypothalamic DEGs of offspring with maternal obesity were not only enriched in the physical functions of the hypothalamus (such as neurodevelopment and metabolic hormone regulation) but also in immune system regulation. The hypothalamic DEGs related to maternal obesity were primarily enriched in "negative regulation of immune system process,"…”
Section: Maternal Obesity Causes the Hypothalamic Inflammation In Off...mentioning
confidence: 44%
See 1 more Smart Citation
“…32 A prospective human dual-cohort study observed an approximately linear association between maternal pre-pregnancy BMI and offspring hypothalamic microstructure on MRI images, further demonstrating the plasticity of prenatal hypothalamic development in the context of maternal overnutrition during pregnancy. 33 Interestingly, in the present study, the hypothalamic DEGs of offspring with maternal obesity were not only enriched in the physical functions of the hypothalamus (such as neurodevelopment and metabolic hormone regulation) but also in immune system regulation. The hypothalamic DEGs related to maternal obesity were primarily enriched in "negative regulation of immune system process,"…”
Section: Maternal Obesity Causes the Hypothalamic Inflammation In Off...mentioning
confidence: 44%
“… 32 A prospective human dual‐cohort study observed an approximately linear association between maternal pre‐pregnancy BMI and offspring hypothalamic microstructure on MRI images, further demonstrating the plasticity of prenatal hypothalamic development in the context of maternal overnutrition during pregnancy. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Notably, prospective studies demonstrate that early rapid weight gain heightens obesity risk throughout life 12 . In addition, while previous neonatal imaging studies have proposed interindividual differences in axonal outgrowth as the cellular underpinnings of the observed variation in hypothalamic mean diffusivity, 11,16 we suggest an alternative interpretation based on these findings that this variation may also be reflective of an inflammatory response within the glial cells of the MBH. In a manner consistent with rodent models, non‐human primate studies demonstrate that in utero exposure to maternal high‐fat diet leads to hypothalamic inflammation/gliosis in 3rd trimester foetuses, and small birth weight coupled with postnatal catch‐up growth 10,17 …”
Section: Discussionmentioning
confidence: 64%
“…Two extant studies have shown that the altered functional connectivity in reward processing and cognitive control, similarly to that observed in obese adults, was also observed in 2-week-old infants with mothers who had high BMI 21,22 . In addition, decreased white matter integrity 23 and increased mean diffusivity in hypothalamus 24 were observed in infants born to mothers with high BMI. Diffusion tensor imaging (DTI) has been an indispensable method to study the white matter, since it provides quantitative scalar values to assess the microstructural integrity.…”
Section: Introductionmentioning
confidence: 98%